Parallel G-triplexes and G-hairpins as potential transitory ensembles in the folding of parallel-stranded DNA G-Quadruplexes - Petr Stadlbauer; Petra Kührová; Lukáš Vicherek; Pavel Banáš; Michal Otyepka; Lukáš Trantı́rek; Jiřı́ Šponer (2019)
Guanine quadruplexes (G4s) are non-canonical nucleic acids structures common in important genomic regions. Parallel-stranded G4 folds are the most abundant, but their folding mechanism is not fully understood. Recent research highlighted that G4 DNA molecules fold via kinetic partitioning mechanism dominated by competition amongst diverse long-living G4 folds. The role of other intermediate species such as parallel G-triplexes and G-hairpins in the folding process has been a matter of debate. Here, we use standard and enhanced-sampling molecular dynamics simulations (total length of ∼0.9 ms) to study these potential folding intermediates. We suggest that parallel G-triplex per se is rather an unstable species that is in local equilibrium with a broad ensemble of triplex-like structures. The equilibrium is shifted to well-structured G-triplex by stacked aromatic ligand and to a lesser extent by flanking duplexes or nucleotides. Next, we study propeller loop formation in GGGAGGGAGGG, GGGAGGG and GGGTTAGGG sequences. We identify multiple folding pathways from different unfolded and misfolded structures leading towards an ensemble of intermediates called cross-like structures (cross-hairpins), thus providing atomistic level of description of the single-molecule folding events. In summary, the parallel G-triplex is a possible, but not mandatory short-living (transitory) intermediate in the folding of parallel-stranded G4.